Reactions of o-aminothiophenol and o-aminophenyl disulfide with itaconic anhydride and (-)-dimenthyl itaconate: access to enantiomerically pure 1,5-benzothiazepines and benzothiazolyl-2-methylacrylic acid - Baag, Md. Merajuddin; Sahoo, Manoj Kumar; Puranik, Vedavati G.; N. P. Argade (Synthesis-Stuttgart, 2007)
{A facile chemo- and regioselective reactions of o-aminothiophenol (o-ATP) with itaconic anhydride is described. 1,5-Benzothiazepinyl-3-acetic acid is obtained in 81% yield via the exclusive Michael type addition of the thiol unit from o-ATP to the carbon-carbon double bond in itaconic anhydride followed by an intramolecular anhydride ring opening with an amine unit. The moderately stereoselective Michael type addition of the thiol unit from o-ATP to (-)-dimenthyl itaconate to obtain a mixture of diastereomers in a 7:3 ratio in 82% yield has been demonstrated. The reductive sulfur-sulfur bond cleavage in the dicarboxylic acid, 2({2-[2-(3-carboxybut-3-enoylamino)phenyidisulfanyl]phenylcarbamoyl\
Keywords: Magnetic nanoparticles; magnetic properties; spin glasses

Reversed reactivity of anilines with alkynes in the rhodium-catalysed C-H activation/carbonylation tandem - Midya, Siba Prasad; Sahoo, Manoj Kumar; Landge, Vinod Gokulkrishna; Rajamohanan, P. R.; Balaraman, Ekambaram (Nature Communications, 2015)
Development of multicatalytic approach consisting of two or more mechanistically distinct catalytic steps using a single-site catalyst for rapid and straightforward access of structurally complex molecules under eco-benign conditions has significance in contemporary science. We have developed herein a rhodium-catalysed C-H activation strategy which uses an unprotected anilines and an electron-deficient alkynes to C-C bonded products as a potential intermediate in contrast to the archetypical C-N bonded products with high levels of regioselectivity. This is followed by carbonylation of C-H bond activated intermediate and subsequent annulation into quinolines has been described. This rhodium-catalysed auto-tandem reaction operates under mild, environmentally benign conditions using water as the solvent and CO surrogates as the carbonyl source with the concomitant generation of hydrogen gas. The strategy may facilitate the development of new synthetic protocols for the efficient and sustainable production of chemicals in an atom-economic way from simple, abundant starting materials.

Reverse-hydroformylation: a missing reaction explored - Nandakumar, Avanashiappan; Sahoo, Manoj Kumar; Balaraman, Ekambaram (Organic Chemistry Frontiers, 2015)
Recent progress in transition-metal catalysed acceptor- and acceptorless-reverse hydroformylation of aldehydes for the conversion of olefins has been discussed. The aldehyde feedstock serves as a source for production of syngas and valuable alkenes.